Test–Retest Reliability of Skill Tests in the F-MARC Battery for Youth Soccer Players. Issue 5 (October 2019) - Padrón-Cabo, Alexis; Rey, Ezequiel; Pérez-Ferreirós, Alexandra; Kalén, Anton
This study aimed to evaluate the test–retest reliability of soccer skill tests belonging to the F-MARC test battery. To avoid bias during talent identification and development, coaches and scouts should be using reliable tests for assessing soccer-specific skills in young male players. Fifty-two U-14 outfield male soccer players performed F-MARC soccer skill tests on two occasions, separated by 7 days. After familiarization, we administered two trial sessions of five skill tests: speed dribbling, juggling, shooting, passing, and heading. We assessed absolute reliability by expressing the standard error of measurement as a coefficient of variation with 95% limits of agreement, and we assessed relative reliability with the intraclass correlation coefficient and with Pearson's correlation ( r ). The results demonstrated satisfactory relative and absolute reliability for speed dribbling, right foot juggling, short passing, shooting a dead ball right, shooting from a pass, heading in front, and heading right. However, reliability values for left foot juggling, chest-head-foot juggling, head-left-foot-right foot-chest-head juggling, long pass, and shooting a dead ball left tests were not strong enough to suggest their usage by coaches in training or sport scientists in research.